Expert survey and classification of tools for modeling and simulating hybrid energy networks. (December 2022) - Widl, Edmund; Cronbach, Dennis; Sorknæs, Peter; Fitó, Jaume; Muschick, Daniel; Repetto, Maurizio; Ramousse, Julien; Ianakiev, Anton
Abstract: Sector coupling is expected to play a key role in the decarbonization of the energy system by enabling the integration of decentralized renewable energy sources and unlocking hitherto unused synergies between generation, storage and consumption. Within this context, a transition towards hybrid energy networks (HENs), which couple power, heating/cooling and gas grids, is a necessary requirement to implement sector coupling on a large scale. However, this transition poses practical challenges, because the traditional domain-specific approaches struggle to cover all aspects of HENs. Methods and tools for conceptualization, system planning and design as well as system operation support exist for all involved domains, but their adaption or extension beyond the domain they were originally intended for is still a matter of research and development. Therefore, this work presents innovative tools for modeling and simulating HENs. A categorization of these tools is performed based on a clustering of their most relevant features. It is shown that this categorization has a strong correlation with the results of an independently carried out expert review of potential application areas. This good agreement is a strong indicator that the proposed classification categories can successfully capture and characterize the most important features of tools for HENs. Furthermore, it allows to provide a guideline for early adopters to understand which tools and methods best fit the requirements of their specific applications. Highlights: A survey of available tools for assessing hybrid energy networks has been performed A set of classification categories has been developed for classifying these tools The classification results reveal different types of methods and tools The types of tools are characterized by their usefulness for different applications